Continued evolution of Jakobshavn Isbrae following its rapid speedup - Joughin, Ian; Howat, Ian M.; Fahnestock, Mark; Smith, Ben; Krabill, William; Alley, Richard B.; Stern, Harry; Truffer, Martin (Journal of Geophysical Research: Earth Surface, 2008)
ISSN:0022-1406 ISSN:0148-0227 ISSN:0196-6928 ISSN:0196-6936 ISSN:2156-2202